Expression and Role of the Intermediate-Conductance Calcium-Activated Potassium Channel KCa3.1 in Glioblastoma. (17th May 2012) - Catacuzzeno, Luigi; Fioretti, Bernard; Franciolini, Fabio
Abstract : Glioblastomas are characterized by altered expression of several ion channels that have important consequences in cell functions associated with their aggressiveness, such as cell survival, proliferation, and migration. Data on the altered expression and function of the intermediate-conductance calcium-activated K (KCa3.1) channels in glioblastoma cells have only recently become available. This paper aims to (i) illustrate the main structural, biophysical, pharmacological, and modulatory properties of the KCa3.1 channel, (ii) provide a detailed account of data on the expression of this channel in glioblastoma cells, as compared to normal brain tissue, and (iii) critically discuss its major functional roles. Available data suggest that KCa3.1 channels (i) are highly expressed in glioblastoma cells but only scantly in the normal brain parenchima, (ii) play an important role in the control of glioblastoma cell migration. Altogether, these data suggest KCa3.1 channels as potential candidates for a targeted therapy against this tumor.